Weighted Estimates for Toeplitz Operators Related to Pseudodifferential Operators. (3rd April 2016) - Lin, Yan; Liu, Zongguang; Xu, Chengdan; Ren, Zichu
Abstract : The authors establish the weighted L p estimates for a class of pseudodifferential operators for both cases 1 < p < ∞ and p = 1, where the weight class is bigger than the classical Muckenhoupt's weight class. Moreover, the weighted estimates for the Toeplitz operators related to pseudodifferential operators are also obtained. As their special cases, the corresponding results for the commutators of pseudodifferential operators can be deduced.